The Relationship between Recurrence Rate and Molecular Subtypes of Breast Cancer in Locally Advance Breast Cancer (LABC) Post Mastectomy: Focus on Comparison of Luminal A and Luminal B - Eric Hartoyo Salim; Eddy Herman Tanggo; Dwi Hari Susilo (HM Publisher, 2021)
Background. Breast cancer is the highest prevalence of malignancy for women in Indonesia and important national health problem. Estimated 2 million women developed breast cancer in 2018 with a mortality rate of 14.1 in every 100,000 women. Regarding the relationship between subtypes and breast cancer recurrence Several studies on gene expression have shown several subtypes of breast cancer, including the two most important subtypes, estrogen receptor (ER) positive (Luminal A and Luminal B) and ER negative (Triple negative and Her2 positive). Based on the explanation above, currently there is no data in Soetomo Hospital that discusses the role of breast cancer subtypes as a prognostic factor in determining the recurrence rate in locally advanced breast cancer.Methods. The research design is an associative test using a retrospective cohort observational analytical study design, associating the relationship between tumor subtypes with recurrence in locally advanced breast cancer patients after mastectomy and has received additional therapy according to standard procedures at Dr. Soetomo Surabaya This study used secondary data from the medical records of the Oncology Polyclinic, RSUD Dr. Soetomo Surabaya from 2014 to 2019.Results. The research subjects who have been selected according to inclusion criteria are 214 people, with the proportion in the population of luminal A and luminal B subtypes of 107 people each. Based on this study, it was found that the subtype was positively correlated with recurrence in LABC patients who had undergonecmastectomy with a significance value of p = 0.000 (p <0.05; 99% CI).Conclusion. There is a relationship between the recurrence rate and the molecular subtype of breast cancer in locally advanced breast cancer (LABC) patients after mastectomy at Dr Soetomo Hospital.